ADAPTASI KOMUNIKASI ANTARBUDAYA PAPUA DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Syahrani, Andi Syafirah; Arni; Manggaga, Indah Pratiwi; Syukri (Communication and Islamic Broadcasting Studies IAIN Parepare, 2025)
The purpose of this study was to determine the forms of intercultural communication adaptation and identify the obstacles faced by Papuan students in adapting to the campus environment. This study used a qualitative approach with a focus on the adaptation experiences of Papuan students. Data were obtained through in-depth interviews with Papuan students who had studied for at least one year at the Muhammadiyah University of Makassar. The results of the study showed that Papuan students faced various adaptation challenges, especially in terms of language and cultural differences. The forms of adaptation carried out included adjusting communication styles, learning local languages, and efforts to understand local cultural values. The main obstacles encountered were difficulties in understanding local dialects, differences in communication methods, and challenges in building social interactions with other students. This study contributes to the understanding of the process of intercultural communication adaptation and can be a reference in developing adaptation for students from different cultural backgrounds.